2022
DOI: 10.55133/eji.290305
|View full text |Cite
|
Sign up to set email alerts
|

Disheveled EGL-10 and pleckstrin domain-containing 5 rs1012068 T/G gene polymorphism among Egyptian chronic HCV-infected patients: disease progression and related complications

Abstract: Hepatitis C virus (HCV) infection related complications including fibrosis, cirrhosis and hepatocellular carcinoma (HCC) are influenced by host genetic factors. Identification of emerging host genetic variations is of promising value. Disheveled EGL-10 and pleckstrin domain-containing 5 (DEPDC5) rs1012068 T/G gene polymorphism has been implicated in liver disease. This study aimed to assess DEPDC5 rs1012068 T/G gene polymorphism with disease progression and related complications among Egyptian patients with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…No relevant case-control studies were identifed based on the alternative polymorphism IDs for rs1012068 (rs56511012, rs58339834, rs386510025) or for rs5998152 (rs61578881, rs8143107). A total of 11 studies [12][13][14][15][16][17][18][19][20][21][22] investigated rs1012068, and 3 studies [12,15,23] investigated rs5998152. Te distribution of genotypes in controls was consistent with Hardy-Weinberg equilibrium (HWE).…”
Section: Characteristics Of Primary Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…No relevant case-control studies were identifed based on the alternative polymorphism IDs for rs1012068 (rs56511012, rs58339834, rs386510025) or for rs5998152 (rs61578881, rs8143107). A total of 11 studies [12][13][14][15][16][17][18][19][20][21][22] investigated rs1012068, and 3 studies [12,15,23] investigated rs5998152. Te distribution of genotypes in controls was consistent with Hardy-Weinberg equilibrium (HWE).…”
Section: Characteristics Of Primary Studiesmentioning
confidence: 99%
“…rs1012068 and HCC Risk. As shown in Table 2 and Figure S1, a meta-analysis based on a population of 2,609 cases and 8,171 in 11 studies [12][13][14][15][16][17][18][19][20][21][22] revealed that the rs1012068 polymorphism did not signifcantly increase HCC risk in total under the allelic model (OR � 1.32, 95% CI � 1.04-1.67, P � 0.02); the recessive model (OR � 1.42, 95% CI � 0.96-2.10, P � 0.08); the dominant model (OR � 1.43, 95% CI � 1.09-1.87, P � 0.01); the homozygous model (OR � 1.61, 95% CI � 1.01-2.57, P � 0.05); or the heterozygous model (OR � 1.39, 95% CI � 1.09-1.79, P � 0.009).…”
Section: Quantitative Data Synthesismentioning
confidence: 99%
See 3 more Smart Citations